New model of competition in education as a basis for forming web project teams - Elena Kozyreva (Voprosy obrazovaniya / Educational Studies Moscow, 2010)
This is a continuation of the article Co-operative model of innovation competitions in pedagogics as a mechanism of reform advancement in education published in no 3 of Issues in Education in 2008. The previous article dealt with the eff ectiveness of competitive and cooperative models from the viewpoint of their correspondence to managerial expectations of the organizers. The present article describes the results of development and trial of co-organizing competition model in the framework of the project ‘Introducing computers in education’ in Krasnoyarsk region in 2005–2008.